Increasing Student Satisfaction Through Improving Service Quality at Tourism Colleges in East Jakarta - Setyo Widiarto; Soerjanto Soerjanto (Majalah Ilmiah Bijak, 2023)
At private universities in East Jakarta, this study examines the impact of five service quality factors on student satisfaction. The research instrument consists of 28 questions arranged and structured based on variables, dimensions and indicators using the Likert scale. Data collection using questionnaires distributed via Google form to 30 people for validity and reliability testing and 300 people as research samples. The multiple linear regression method is used for data analysis with the help of SPSS software. The study's results partially show that three service quality dimensions, namely Reliability, Empathy and tangibles, significantly affect student satisfaction. Still, the dimensions of Responsiveness and assurance do not affect student satisfaction. Simultaneously, five dimensions of service quality have a significant effect on student satisfaction.